2009
DOI: 10.1063/1.3293082
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Core Heating from Merging Subclusters

Abstract: Abstract. Though feedback from central active galactic nuclei provides an attractive solution to the problem of overcooling in galaxy cluster cores, another possible source of heating may come from "sloshing" of the cluster core gas initiated by mergers. We present a set of simulations of galaxy cluster mergers with subclusters in order to determine the amount of heating provided by the mechanism of sloshing, exploring a parameter space over mass ratio, impact parameter, and viscosity of the intracluster mediu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
2
6
0
Order By: Relevance
“…We find good qualitative agreement of our map to a model cluster selected from a suite of hydrodynamical simulations by ZuHone et al (2009). This particular simulated cluster had recently undergone an off-axis merger with a high mass ratio (∼ 10 : 1).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We find good qualitative agreement of our map to a model cluster selected from a suite of hydrodynamical simulations by ZuHone et al (2009). This particular simulated cluster had recently undergone an off-axis merger with a high mass ratio (∼ 10 : 1).…”
Section: Discussionsupporting
confidence: 66%
“…Objects once thought to be spherically symmetric and relaxed have been shown to display evidence of interesting phenomena which provide insight to the complicated dynamics at play in these structures. Among these are shocks and cold-fronts induced by recent mergers (e.g., Markevitch & Vikhlinin 2007), cavities and heating caused by AGN interactions (e.g., Mc-Namara et al 2005) and sharp surface brightness edges caused by gas sloshing (e.g., ZuHone et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the impact parameter is expected to be small, as suggested by the rather symmetric SB roughly in the N-S direction (in contrast to the asymmetric SB in the E-W direction) in Figure 1a. The observed intensity and temperature maps look similar to the first passage of a minor merger with a low impact parameter (e.g., see simulations of the R=1:10 and b=0 case right after the passage through the center by ZuHone & Kowalik et al 2016). Although no small, secondary galaxy is observed near the position of the front, it should be noted that a small system could be difficult to detect if it falls behind NGC 1132 or has been tidally disrupted by the encounter.…”
Section: B Recent Minor Merger With a Low Impact Parametersupporting
confidence: 54%
“…(3) The collision produces an expanding impact disc of gas as two clusters pass through each other which breaks into two sections continuing outwards with the main masses. Zu Hone, Lamb & Ricker (2009) have discussed ring formation. The dark matter components pass through each other and the core regions are not disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to identify the CC as a result of the cluster’s merger, but O’Hara et al (2006) argued that major mergers do not evolve CCs from their study of the scatter in scaling relations. However, Zu Hone & Markevitch (2009) found that ‘sloshing’ produced in mergers could be a source of heating in cluster cores.…”
Section: Mass Estimates Of the Two Clumpsmentioning
confidence: 99%